Capital flows and financial stability in emerging economies. - Pundit, Madhavi (Metro Manila, Philippines Asian Development Bank, 2017)
The findings suggest that, after controlling for several macroeconomic factors, there are significant effects of different gross capital flow measures on the financial stability proxies, but they are not homogeneous across economies and across flow types. The paper proposes several country-specific financial and macroeconomic characteristics to help explain these differences.
Keywords: Finance -- Economic aspects; Electronic books